Peran Divisi Human Capital dalam Meningkatkan Kinerja Karyawan Corporate Social - Moulia Putri Utami; Rahmat Salam (Student Scientific Creativity Journal, 2024)
The role of Human Capital Division is very influential in improving the employee performance Corporate Social Responsibility (CSR) of Head Office PT ANTAM Tbk South Jakarta. These significant results are based on investment in increasing employee skills, knowledge and experience which makes employees the capital or assets of a company which is the focus of improving employee performance. The purpose of this research is to find out the role of Human Capital Division in improving the employee performance Corporate Social Responsibility (CSR) of Head Office PT ANTAM Tbk South Jakarta. In this research, the author used a qualitative descriptive research method to develop a theory that was built when obtaining data in the field using data collection techniques in the form of observation, interviews and documentation. The research results show that increasing employee performance is a significant result of the role of the human capital division based on aspects of work quality, work quantity, task implementation and responsibility which are the focus of improving employee performance. The author's findings show that the emphasis on skills achieved through the recruitment process is the main thing. The human capital division ensures that the employees recruited have the skills necessary to make maximum contributions to the programs implemented by CSR. Increasing employee performance is achieved through various factors related to the role of the human capital division of PT ANTAM Tbk South Jakarta Head Office, such as providing training that is relevant to employee duties and responsibilities, not only increasing an employee's competency but also forming a strong foundation for increasing productivity. Regular evaluation also has a positive impact on improving employee performance, where there will be input and encouragement for each employee. This also makes employees open to each other so that communication is established well and loyalty is created between employees. Overall, this thesis confirms that the human capital division has an important role in improving employee performance. This is also formed from employees who are competent and willing to continue to improve their abilities and skills.